Pancasila Student Profile Strengthening Project: Self-Efficacy and Its Influence on Primary School Students' Motivation to Engage in Citizenship Issues - Muh Rifqienur Adiwardana; Herwin; Fathiyah Indah (Jurnal Ilmiah Sekolah Dasar, 2024)
Good self-efficacy is a key factor in enhancing students' motivation to engage in citizenship issues. This study aims to analyze the impact of students' self-efficacy, resulting from the Pancasila student profile strengthening project in primary schools, on students' motivation to engage in citizenship issues. This quantitative research employs a survey method. The population consists of fifth-grade primary school students, with all 45 students in this grade serving as the sample. Data were collected using a self-efficacy questionnaire developed based on the Pancasila student profile competencies and a student motivation questionnaire based on the characteristics of citizenship engagement. The data were analyzed using simple linear regression analysis. The results showed a regression coefficient significance of 0.00, and the regression equation Y = 0.347X + 36.968, indicating that students' motivation to engage in citizenship issues increases by 0.347 for each unit of self-efficacy. Self-efficacy contributed 24.1% to students' motivation to engage in citizenship issues. Based on these findings, it can be concluded that students' self-efficacy, derived from the Pancasila student profile strengthening project, positively influences their motivation to engage in citizenship issues.